To rewrite the equation \( \frac{4x}{3x - 12} + 3 = 10 \) in the form of two equations joined by "and," we can isolate the fraction on one side and the constant on the other.
-
First, we can rewrite the equation by isolating the fraction: \[ \frac{4x}{3x - 12} = 10 - 3 \]
-
This simplifies to: \[ \frac{4x}{3x - 12} = 7 \]
Now we can express this as two equations:
-
The first equation representing the fraction: \[ \frac{4x}{3x - 12} = 7 \]
-
The second equation representing the simplification: \[ 10 - 3 = 7 \]
Thus, we can write it as: \[ \frac{4x}{3x - 12} = 7 \quad \text{and} \quad 10 - 3 = 7 \]